Detection of Alpha- and Betacoronaviruses in Miniopterus fuliginosus and Rousettus leschenaultii, two species of Sri Lankan Bats - Muzeniek, Therese; Perera, Thejanee; Siriwardana, Sahan; Bas, Dilara; Kaplan, Fatimanur; Öruc, Mizgin; Becker-Ziaja, Beate; Schwarz, ranziska; Premawansa, Gayani; Premawansa, Sunil; Perera, Inoka C.; Yapa, Wipula B (My University, 2021)
Bats are known to be potential reservoirs of numerous human-pathogenic viruses. They have been identified as natural hosts for coronaviruses, causing Severe Acute Respiratory Syndrome (SARS) in humans. Since the emergence of SARS-CoV-2 in 2019 interest in the prevalence of coronaviruses in bats was newly raised. In this study we investigated different bat species living in a sympatric colony in the Wavul Galge cave (Koslanda, Sri Lanka). In three field sessions (in 2018 and 2019), 395 bats were captured (Miniopterus, Rousettus, Hipposideros and Rhinolophus spp.) and either rectal swabs or fecal samples were collected. From these overall 396 rectal swab and fecal samples, the screening for coronaviruses with nested PCR resulted in 33 positive samples, 31 of which originated from Miniopterus fuliginosus and two from Rousettus leschenaultii. Sanger sequencing and phylogenetic analysis of the obtained 384-nt fragment of the RNA-dependent RNA polymerase revealed that the examined M. fuliginosus bats excrete alphacoronaviruses and the examined R. leschenaultii bats excrete betacoronaviruses. Despite the sympatric roosting habitat, the coronaviruses showed host specificity and seemed to be limited to one species. Our results represent an important basis to better understand the prevalence of coronaviruses in Sri Lankan bats and may provide a basis for pursuing studies on particular bat species of interest.
Keywords: bat coronavirus; Miniopterus fuliginosus; Rousettus leschenaultii; Sri Lanka; cave-dwelling; sympatric colony; alphacoronavirus; betacoronavirus